Odpowiedzi

Najlepsza Odpowiedź!
2010-03-08T17:10:15+01:00
A)2a+4=3a
2a-3a= -4
-a= -4/*(-1)
a=4

b)6b+10=46
6b=46-10
6b-36/:6
b=6

c)4t+3=6t
4t-6t=-3
-2t= -3/:(-2)
t=3/2
t=1 i 1/2

d)2y+13=5y+4
2y-5y=4-13
-3y=-9/:(-3)
y=3
1 5 1
2010-03-08T17:10:31+01:00
A)2a+4=3a / -2a
4=a
a=4
b)6b+10=46/-10
6b=36/:6
b=6
c)4t+3=6t/-4t
3=2t/:2
1,5=t
t=1,5
d)2y+13=5y+4/-2y
13=3y+4/-4
9=3y/:3
3=y
y=3

DSZ NAJ :):):)??????????????????///
2010-03-08T17:10:49+01:00
A) 2a+4=3a
a=4

b) 6b+10=46
6b=36 |/6
b=6

c ) 4t+3=6t
3=2t
t=1.5

d) 2y+13=5y+4
9=3y
y=3

to tak to wygląda. ;-)